2018
DOI: 10.1007/s11896-018-9275-z
|View full text |Cite
|
Sign up to set email alerts
|

An Interview Study of the Experiences of Police Officers in Regard to Psychological Contract and Wellbeing

Abstract: In this paper, it is argued that the psychological contract (PC) could provide rich insights into the understanding of employee and employer relations within the police and the stress and wellbeing of officers. Eighteen semi-structured interviews were conducted with active, full-time police officers and these were analysed using framework analysis. More than 100 base-units of meaning were identified which were categorised into six main themes namely 'Motivation', 'Mutual obligations', 'Stressors', 'Negative co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 76 publications
1
33
0
1
Order By: Relevance
“…Furthermore, the phenomenon shows that the police profession is one of the most demanding professions and prone to burnout. This statement is supported by Campbell and Nobel (in Duran et al, 2018) that the police profession is a highly stressful job compared to other professions. Therefore, the police profession is identified as one of the most stressful professions worldwide due officers' exposure to various acute and chronic stressful events in their workplace (Fazeelat Duran et al, 2019).…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Furthermore, the phenomenon shows that the police profession is one of the most demanding professions and prone to burnout. This statement is supported by Campbell and Nobel (in Duran et al, 2018) that the police profession is a highly stressful job compared to other professions. Therefore, the police profession is identified as one of the most stressful professions worldwide due officers' exposure to various acute and chronic stressful events in their workplace (Fazeelat Duran et al, 2019).…”
Section: Discussionmentioning
confidence: 77%
“…This statement is supported by Campbell and Nobel (in Duran et al, 2018) that the police profession is a highly stressful job compared to other professions. Therefore, the police profession is identified as one of the most stressful professions worldwide due officers' exposure to various acute and chronic stressful events in their workplace (Fazeelat Duran et al, 2019). However, based on the results of the study it was found that riot control police officers show low burnout.…”
Section: Discussionmentioning
confidence: 77%
“…To date, the majority of research on psychological health in policing has focused on police officers (Acquadro Maran et al, 2015; Duran et al, 2019; Ma et al, 2015). However, recent research has highlighted that police employees in non-operational roles can often be exposed to traumatic events directly (e.g.…”
mentioning
confidence: 99%
“…In a recent qualitative study with UK. police officers, a major source of police stress was identified as inadequate equipment to perform their duties resulting from austerity cuts (Duran et al, 2019). Duran, Woodhams and Bishopp (2020) also reported stress was linked to how police employees perceive unfairness when their contributions are not fully reciprocated or valued.…”
Section: Emerging Covid19 Researchmentioning
confidence: 99%